PENGEMBANGAN TEKS LAPORAN PENELITIAN DALAM PENYUSUNAN HISTORIOGRAFI SEJARAH - Adilla Aura Putri; Fitri Nurjihan; Rieke Corry Betsena Br. Tarigan; Ika Febriana (Universitas Nias Raya, 2024)
Research reports are important in the preparation of historical writing. Through the research report, we can pour the flow of history that occurs based on historical writing methods, such as heuristics, criticism (verification), interpretation, and historiography (the stage of writing history). By following the historical writing method, it can then be developed and compiled in the form of a research report. The writing of this article uses a descriptive method with a qualitative approach and uses the literature study method. The literature study method is a research method by collecting library data and processing the data. Historiography is the result or work of historical writing. This historiography uses research methods to communicate the results of research that are tested, revealed, and interpreted. Historians in pouring the results of their research into the text of their reports or scientific works must comply with applicable historical writing rules. Historiography is historical writing that is preceded by research (analytical) of events in the past. The subject matter in historiography talks about the history of historical writing or in a more practical context it can be understood.